ANALISIS TREN RAGAM MEDIA PEMBELAJARAN BERBASIS TEORI KONSTRUKTIVISME DALAM PEMBELAJARAN TEMATIK SEKOLAH DASAR UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI SISWA SEKOLAH DASAR - Ayura Rahma Awalia; Dzaki Ullin Nuha Fachrur Rossy; Najwa Fauziah; Nurcholis Fajar Dwi Kurniawan; Oktavia Diah Rahmadhani; Sabrina Wafa; Taufik Muhtarom (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
Technological innovations have driven the diversification of pedagogical instruments in elementary school thematic learning. However, prior studies tend to examine media utilization partially, leaving a significant gap in research that integrates trends, characteristics, and implementation phases of constructivist-based media into a single comprehensive synthesis. This study aims to comprehensively analyze the trends, characteristics, and implementation patterns of learning media based on constructivist theory in elementary school thematic learning. The Systematic Literature Review (SLR) method was applied by adopting the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to screen articles from the Google Scholar database published between 2016 and 2025. Out of 970 identified articles, 25 met the strict inclusion and exclusion criteria for further analysis. The synthesis reveals a distinct shift in media trends, transitioning from conventional-manipulative media to interactive-digital media (such as interactive PowerPoint, animated videos, Android applications, Quizizz, and Wordwall) that are strictly oriented toward students' independent knowledge construction. The core characteristics of these media center on a student-centered approach, visual attractiveness, and contextual relevance, while their implementation systematically follows procedural stages from needs analysis to evaluation. This literature synthesis confirms that the integration of constructivism-based media consistently transforms thematic learning into a more active, meaningful, and adaptive experience aligned with the cognitive development of elementary school students. ABSTRAK Perkembangan inovasi teknologi telah mendorong diversifikasi instrumen pedagogis dalam pembelajaran tematik di sekolah dasar. Namun, literatur terdahulu cenderung mengkaji pemanfaatan media secara parsial, sehingga belum ada kajian yang mengintegrasikan tren, karakteristik, dan tahapan implementasi media berbasis konstruktivisme dalam satu kesatuan sintesis yang utuh. Penelitian ini bertujuan untuk menganalisis secara komprehensif tren ragam, karakteristik, serta pola implementasi media pembelajaran berbasis teori konstruktivisme pada lanskap pembelajaran tematik sekolah dasar. Metode Systematic Literature Review (SLR) diterapkan dengan mengadopsi protokol PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) melalui pangkalan data Google Scholar (2016–2025). Dari total 970 artikel yang tersaring, sebanyak 25 artikel memenuhi kriteria inklusi dan eksklusi untuk dianalisis. Hasil sintesis menunjukkan adanya pergeseran tren media yang linier, bergerak dari media konvensional-manipulatif menuju media digital-interaktif (seperti PowerPoint interaktif, video animasi, aplikasi Android, Quizizz, dan Wordwall) yang berorientasi pada konstruksi pengetahuan mandiri siswa. Karakteristik utama media tersebut bertumpu pada pendekatan student-centered, visibilitas menarik, dan kontekstual. Sementara itu, implementasinya secara konsisten mengikuti pola prosedural analisis kebutuhan hingga evaluasi. Sintesis literatur ini menegaskan bahwa integrasi media berbasis konstruktivisme secara konsisten mampu mentransformasi pembelajaran tematik menjadi lebih aktif, bermakna, dan adaptif terhadap perkembangan kognitif siswa sekolah dasar.